A REVIEW STUDY: ROLE OF ANTIOXIDANTS IN PREVENTION OF MALIGNANCY GROWTH (CANCER) - Mishra, Ayushi; Singh, Pratibha; Agrawal, Monika; Tiwari, Ramanand; Upadhyay, Garima; Byadgi, Parameswarappa S. (International Journal of Psychosocial Rehabilitation, 2024)
Today, Malignancy is a horrendous sickness which is the subsequent driving reason fordeath on the planet. Malignancy is a gathering of numerous sicknesses includinganomalous cell development with uncontrolled cell division, for example, skin disease,cellular breakdown in the lungs, colon disease, prostate malignancy, lymphoma, and so onThe expanding disease trouble is because of a few elements, including populacedevelopment and maturing just as the changing commonness of specific reasons formalignant growth connected to the social and monetary turn of events. Various kinds ofmalignancy have various manifestations and at the same time various medicines. As  indicated by WHO-around sixteen percent of passing overall are because of disease. A feweating regimens forestall the danger of malignancy and there are others that expand thedanger of disease. Along these lines, it is hard to demonstrate which food diminishes thedanger of malignant growth and which nourishments cause disease. Cell reinforcementsensure our cells by annihilating free radicals and help diminish the danger of malignancy.Powerful counteraction endeavours may clarify the noticed decline in occurrence rates forcertain diseases, for example, cellular breakdown in the lungs and cervical malignancy. Inthis article, we will discuss the role of antioxidants in reducing the risk of cancer